S145 Measures of oesophageal impedance are not predictive of lung function decline in interstitial lung disease. (December 2018) - Mackintosh, JA; Adamali, H; Patel, K; Chua, F; Renzoni, EA; Kokosi, M; Kouranos, V; Wells, AU; Molyneaux, PL; Maher, TM; George, PM
Abstract : Background: The role of gastro-oesophageal reflux in the pathogenesis of pulmonary fibrosis is not well established and the beneficial effect of anti-acid therapy remains controversial. This study aimed to examine the influence of objective measures of acid-reflux on lung function decline in patients with interstitial lung disease (ILD). Methods: A retrospective cohort of unselected patients with ILD who underwent 24 hour oesophageal impedance monitoring between 2008 and 2011 were included for analysis. Clinically significant acid reflux was defined according to the 'Lyon Consensus' as an acid exposure time (proportion of time pH <4) of >6% or>80 reflux episodes. Results: Oesophageal impedance was performed in 141 patients (53.2% male, mean age 60 years), 58 with idiopathic pulmonary fibrosis (IPF), 17 hypersensitivity pneumonitis, 7 sarcoidosis, 37 connective tissue disease and 22 with other ILD. Oesophageal impedance was performed a mean of 36 days from the first lung function measurement. Serial lung function was performed a mean of 11±4 months apart (range 1–46 months). Mean change in FVC was greater in IPF patients (−9.0%±17.1%; 235 mL±447 mL) than for non-IPF patients (−1.4%±13.8%; 29 mL±263 mL) (p≤0.001). Clinically significant acid reflux was observed in 68/141 (48%) of all ILD patients, 29/58 (50%) in IPF and 39/83 (47.0%) in non-IPF (p=0.725). A positive oesophageal impedance test was not associated with greater FVC decline overall (p=0.499) or in IPF (p=0.577). The presence of acid reflux was no greater in those with IPF and >10% FVC decline (p=0.482). Mortality was 48/58 (82.8%) in the IPF group and 39/83 (47.0%) in the non-IPF group (p≤0.001). Median survival was 3.0 years in the IPF group and 6.7 years in non-IPF (p≤0.001). There was no association between the presence of acid reflux and mortality overall (p=0.305) or in IPF (p=0.487). Conclusions: In this unselected ILD cohort, clinically significant acid reflux was confirmed in almost 50% of cases. No relationship was observed between acid reflux and lung function decline, potentially explaining the lack of response to anti-acid therapy reported in some studies. Given the inability to control for anti-acid therapy, prospective randomised controlled studies are necessary to confirm these findings. The role of non-acid reflux and impact of hiatus hernia requires further study.